ISIS’s use of cyberspace – furthering the organization’s goals utilizing new media - Raiskin, Or Anat Elimelech (Humaniora. Czasopismo Internetowe, 2019)
ISIS engages a wide array of new media tools: Facebook, Instagram, Twitter, YouTubeand other social media outlets.ISIS uses advanced knowhow, technological innovations, social media, and has even launched applications. This allows it to influence and recruit outside of its physical borders in Syria and Iraq. This paper will describe the various ends motivating ISIS’s usage of new media tools, such as worldwide propagation of ideology, recruitment of personnel and assets, establishing terrorist cells and guiding terror attacks.In addition, this paper will discuss ISIS’s ideology, the underlying religious jurisprudence dissonance and cyber-jihad – the use of technology and cyberspace to advance violent militaristic jihad against the perceived enemies of Islam.